Populism and anti-liberal thought: Lega and M5S in the Italian context - Adinolfi, G. (Populismo: teorias e casos, 2020)
Representation, according to the populist rationale and the way how the relationship between démos and power is established, is the core issue of this article. ~us, it discusses how the populist challenge can a|ect, directly and indirectly, the way the representative and liberal democracy works. ~at is, the focus lies on how the populists build their own audience and on the institutional reshue they propose to enforce the people’s will.